2022
DOI: 10.3390/molecules27154896
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Surface Tension of Deep Eutectic Solvents: A Step Forward in the Use of Greener Solvents

Abstract: Deep eutectic solvents (DES) are an important class of green solvents that have been developed as an alternative to toxic solvents. However, the large-scale industrial application of DESs requires fine-tuning their physicochemical properties. Among others, surface tension is one of such properties that have to be considered while designing novel DESs. In this work, we present the results of a detailed evaluation of Quantitative Structure-Property Relationships (QSPR) modeling efforts designed to predict the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Their model predicted that the lipophilicity, polarizability, and dipole moment of DESs are found to be responsible for ruling their surface tensions. 41 In 2003, Abbott et al reported the first relineF (ChF) DES mixtures (containing 1:2, ChF/Urea), which showed a very low melting temperature of 274 K and strong interactions between fluoride anions and the amino hydrogens of urea. 43 Harmon et al studied the strong OH...F hydrogen bond interactions using ChF in multiple publications.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their model predicted that the lipophilicity, polarizability, and dipole moment of DESs are found to be responsible for ruling their surface tensions. 41 In 2003, Abbott et al reported the first relineF (ChF) DES mixtures (containing 1:2, ChF/Urea), which showed a very low melting temperature of 274 K and strong interactions between fluoride anions and the amino hydrogens of urea. 43 Harmon et al studied the strong OH...F hydrogen bond interactions using ChF in multiple publications.…”
Section: ■ Introductionmentioning
confidence: 99%
“…utilized quantitative structure–property relationship (QSPR) models for predicting density and viscosity of various hydrophobic eutectic solvents using conductor-like screening model for real solvents (COSMO-RS) based descriptors . The group of Halder also estimate the density, surface tension, and CO 2 uptake capability of DESs using QSPR model. Their model predicted that the lipophilicity, polarizability, and dipole moment of DESs are found to be responsible for ruling their surface tensions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Stephens and Smith underlined the importance of interfacial properties and the need for a thorough understanding of them in an interesting review or perspective article . Several studies in the literature have already experimentally measured and theoretically predicted the surface tensions of DESs using techniques, such as quantitative structure–property relationships and machine learning. However, while these methods are intriguing, predicting surface tension through machine learning and thermodynamic laws does not fully reveal the structure of the interface or establish a connection with surface tension. There have been very few reports on molecular or microscopic insights into the surface tension of both pure and aqueous DESs .…”
Section: Introductionmentioning
confidence: 99%